A Descriptive Analysis of Social Media Usage as Predictors of Study Habits among Students with Intellectual Disabilities in Calabar Metropolis: Implications for Inclusive Education - Eburu, Odey Samuel; Ironbar, Virginia Emmanuel; Edu, Grace Onya; Atah, Abanyam Victoria; Emmanuel, Ushie Doris; Ogbeche, Ogar Raymond; Odok, Edmond Asu; Ahueansebhor, Emmanuel; Ukah, Ukah Julius; Ushie, Akpa Stephen; Ingiona, Adie Paul; Omini Eloma, Eloma-Ekpo; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2023)
Aim: This study is a descriptive analysis of Facebook and WhatsApp as predictors of study habits among SSII students with disabilities in Public Secondary Schools of Calabar Metropolis of Cross River State, Nigeria: Implications for inclusive education. Two study objectives were stated to guide the study and achieve its goals. Two research questions were formulated. A literature review was carried out based on the variables under study, as research gaps were also stated. Method: The study utilised the descriptive survey research design. The population of Senior Secondary School II (SSII) students with disabilities in Calabar Metropolis comprises 3,814 from 24 public Secondary Schools. The study used a stratified random sampling technique. Out of 3,814 respondents, 763 respondents were sampled for the study. A validated 15-item four-point modified Likert scale questionnaire was the instrument used for data collection. The face and content validity of the instrument was established by experts in Test and Measurement from the University of Calabar, Calabar-Nigeria. The reliability estimates of 0.82 for the instruments were established using the Cronbach Alpha method. A descriptive analysis of frequency, percentages, mean, and standard deviation was used to test the research questions posed for the study. Results: The results obtained from the data analysis revealed there is a high extent of the impact of Facebook on study habits among SSII students with disabilities, and there is also a high extent of the impact of WhatsApp on study habits among SSII students with disabilities in Public Secondary Schools of Calabar Metropolis of Cross River State, Nigeria Conclusion: Based on the study’s findings, it was concluded that Facebook and WhatsApp utilisation significantly impact study habits among SSII students with disabilities in Public Secondary Schools in the study area. Recommendation: Based on the result of the study, it was recommended that there should be a continuity of inclusive education policies and social media usage in Cross River State and Nigeria at large.